(untitled) (Research, Society and Development, 2023)
Hyperpigmentation of the skin, commonly called melasma, is a condition without a clear cause located on the face and characterized by irregular patches with a high degree of vascularity, intense brown coloration resulting from the deposition of melanin derived from the oxidation of tyrosine in melanocytes located in the basal layer of the epidermis. Although affecting both sexes, it occurs more frequently in women. Analyses indicate that a tranexamic acid is an option for melasma care, even though the available treatments do not have absolute efficacy. The objective of this article is to report on the action of tranexamic acid and its oral administration routes, with or without other treatment methods. The methodology used was an integrative review of double-blind studies, selecting 86 articles between 2012 and 2022, and applying inclusion and exclusion criteria. The results indicate that oral tranexamic acid is effective and has low side effects, which favors patient adherence to treatment, concluding that this therapy can be a promising option for melasma treatment.